Unravelling microRNA regulation and miRNA-mRNA regulatory networks in osteogenesis driven by 3D nanotopographical cues - Balachander G.M.; Nilawar S.; Meka S.R.K.; Ghosh L.D.; Chatterjee K. (My University, 2025)
Three-dimensional (3D) culturing of cells is being adopted for developing tissues for various applications such as mechanistic studies, drug testing, tissue regeneration, and animal-free meat. These approaches often involve cost-effective differentiation of stem or progenitor cells. One approach is to exploit architectural cues on a 3D substrate to drive cellular differentiation, which has been shown to be effective in various studies. Although extensive gene expression data from such studies have shown that gene expression patterns might differ, the gene regulatory networks controlling the expression of genes are rarely studied. In this study, we profiled genes and microRNAs (miRNAs) via next-generation sequencing (NGS) in human mesenchymal stem cells (hMSCs) driven toward osteogenesis via architectural cues in 3D matrices (3D conditions) and compared with cells in two-dimensional (2D) culture driven toward osteogenesis via soluble osteoinductive factors (OF conditions). The total number of differentially expressed genes was smaller in 3D compared to OF conditions. A distinct set of genes was observed under these conditions that have been shown to control osteogenic differentiation via different pathways. Small RNA sequencing revealed a core set of miRNAs to be differentially expressed under these conditions, similar to those that have been previously implicated in osteogenesis. We also observed a distinct regulation of miRNAs in these samples that can modulate gene expression, suggesting supplementary gene regulatory networks operative under different stimuli. This study provides insights into studying gene regulatory networks for identifying critical nodes to target for enhanced cellular differentiation and reveal the differences in physical and biochemical cues to drive cell fates. © 2024 The Royal Society of Chemistry.